2014
DOI: 10.1108/ijse-08-2012-0142
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ attitudes toward insurance frauds: an application of Adams’ equity theory

Abstract: Purpose – Although research on insurance frauds has found that deductible amount influences customers’ attitudes toward insurance frauds, very little work has further investigated the roles of deductible-premium ratios and insurance experiences. Building on the foundations of Adams' equity theory, the authors examined the impact of the deductible-premium ratios on customers' attitudes toward insurance frauds. The authors also studied the relationship among the experience of applying claims, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
0
20
0
2
Order By: Relevance
“…The first stream of research is concerned with specific behaviors, such as shoplifting (e.g., B.T. Smith & Clarke, ), digital piracy (e.g., Aleassa, Pearson, & McClurg, ) or insurance fraud (e.g., Miyazaki, ; Tseng & Kuo, ). By examining attitude, intention, and/or behavior in one specific context, these studies can help understand the complexity of cognitive decision‐making mechanisms.…”
Section: Consumer Ethically Questionable Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…The first stream of research is concerned with specific behaviors, such as shoplifting (e.g., B.T. Smith & Clarke, ), digital piracy (e.g., Aleassa, Pearson, & McClurg, ) or insurance fraud (e.g., Miyazaki, ; Tseng & Kuo, ). By examining attitude, intention, and/or behavior in one specific context, these studies can help understand the complexity of cognitive decision‐making mechanisms.…”
Section: Consumer Ethically Questionable Behaviormentioning
confidence: 99%
“…By examining attitude, intention, and/or behavior in one specific context, these studies can help understand the complexity of cognitive decision‐making mechanisms. In insurance industry studies, for example, customer perception of unfairness is shown to be important because “unfair treatment” by an insurer appears to increase the likelihood of customer insurance fraud (Tseng & Kuo, ). The second stream of research engages in more holistic accounts, giving a wider picture of ethically questionable consumer behavior and simultaneously exploring different ethical situations.…”
Section: Consumer Ethically Questionable Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, accurate information regarding the policy which will be bought by consumers should be provided by insurance organizations in order to avoid confusion on the offers provided. Therefore, honesty between consumers and insurance organizations is important as the factor preventing consumers from committing insurance claim fraud (Tseng & kuo, 2014;Burhan, Salleh, & Burhan, 2015) Based on the theory's attribution, the cause and the effect which influence customers' decisionmaking in this matter are related to each other. This is due to its attribution for evaluation of consumers' perception on the assessment of price .…”
Section: Consumer Behaviourmentioning
confidence: 99%
“…This concept was accentuated by Adams (1963), who wrote on the development of the Equity theory that workers are motivated by the sense that machinations in their workplace or other organization are fair and equitable (Tseng & Kuo, 2014). The Equity Theory was established by Adams (1963) to explain the socio-psychological motivation in relational terms primarily in the workplace regarding fairness and equity (Burrai, Font, & Cochrane, 2015).…”
Section: History Of Related Theories Up To the Application Of Servantmentioning
confidence: 99%